Politeness Phenomena in A Symmetrical Social Relation of The Participants of Heritage Language Cultures of West Sulawesi - Muthmainnah Mursidin; Ida Ilmiah Mursidin; Rizka Indahyanti (Universitas Muhammadiyah Enrekang, 2022)
ABSTRACT The research is aimed at verifying this basic assumption by studying the politeness phenomena of the heritage language culture of West Sulawesi, Indonesia. The research is descriptive quantitative in nature utilizing a newly prospective model of politeness theoretical framework developed by the author called social relation symmetricity model. Data were collected from 3 respondents of the heritage language culture of West Sulawesi, Indonesia; Mandarese mostly through questionnaires. The study found that in a symmetrical social relation of the participants, the data analysis obviously denoted a regular distinctive pattern of politeness governed by ages. When talking for instance to older interlocutors (friends, strangers, employees, and relatives), the participants prefer using a more deferent variety and as such applying ‘negative politeness strategy’ (Brown & Levinson, 1987). In contrast, when talking to interlocutors of the same ages (friends and relatives), the participants tend to employ a more casual variety and as such applying ‘positive politeness strategy’ (ibid, 1987). Such a crucial role of ages was also denoted in an asymmetrical relation of the participants. Hence, the study concludes that ages have been the most significant social variables of power governing the participants’ politeness strategies of the heritage language cultures of West Sulawesi ethnic groups under study.